(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Objectives: The objective of this study was to explore the presence of risk factors among the female patients of a tertiary care hospital in old Dhaka city. Study design: Cross sectional study. Place and duration of the study: From February 2011 to January 2012 in Cardiology In-Patient Department in Dhaka National Medical Institute Hospital. Sampling technique with sample size: Convenient sampling technique was adopted with the sample size 201. Methodology: Written pre-tested interviewer administered questionnaires, stethoscope, sphygmomanometer; measuring tape and weight measuring machine were used as data collection tools. Data were collected by face to face interview, from the records of reports and physical examinations. Results: Higher portion of respondents (31.8%) were in 51-60 years of age. More than two-thirds (70%) of the respondents were menopausal and one-tenth were taking hormone replacement therapies. Almost all of the fertile female respondents were taking oral contraceptive pills. More than two-third of the respondents (74.1%) were hypertensive. Only one-third (32.8%) exercised regularly and more than half of the respondents (51.8%) had more than normal BMI. Conclusion and recommendation: The study findings suggested the vulnerability of female to coronary heart diseases. Therefore, steps should be taken in increasing the awareness about coronary heart diseases among the female. J. Dhaka National Med. Coll. Hos. 2014;20(01):50-53